A randomized controlled trial evaluating combination detection of HIV in Malawian sexually transmitted infections clinics. Issue 4 (30th April 2021) - Chen, Jane S; Matoga, Mitch; Pence, Brian W; Powers, Kimberly A; Maierhofer, Courtney N; Jere, Edward; Massa, Cecilia; Khan, Shiraz; Rutstein, Sarah E; Phiri, Sam; Hosseinipour, Mina C; Cohen, Myron S; et al.
Abstract: Introduction: HIV diagnosis is the necessary first step towards HIV care initiation, yet many persons living with HIV (PLWH) remain undiagnosed. Employing multiple HIV testing strategies in tandem could increase HIV detection and promote linkage to care. We aimed to assess an intervention to improve HIV detection within socio‐sexual networks of PLWH in two sexually transmitted infections (STI) clinics in Lilongwe, Malawi. Methods: We conducted a randomized controlled trial to evaluate an intervention combining acute HIV infection (AHI) screening, contract partner notification and social contact referral versus the Malawian standard of care: serial rapid serological HIV tests and passive partner referral. Enrolment occurred between 2015 and 2019. HIV‐seropositive persons (two positive rapid tests) were randomized to the trial arms and HIV‐seronegative (one negative rapid test) and ‐serodiscordant (one positive test followed by a negative confirmatory test) persons were screened for AHI with HIV RNA testing. Those found to have AHI were offered enrolment into the intervention arm. Our primary outcome of interest was the number of new HIV diagnoses made per index participant within participants' sexual and social networks. We also calculated total persons, sexual partners and PLWH (including those previously diagnosed) referred per index participant. Results: A total of 1230 HIV‐seropositive persons were randomized to the control arm, and 561 to the intervention arm. Another 12, 713 HIV‐seronegative or ‐serodiscordant persons underwent AHI screening, resulting in 136 AHI cases, of whom 94 enrolled into the intervention arm. The intervention increased the number of new HIV diagnoses made per index participant versus the control (ratio: 1.9; 95% confidence interval (CI): 1.2 to 3.1). The intervention also increased the numbers of persons (ratio: 2.5; 95% CI: 2.0 to 3.2), sexual partners (ratio: 1.7; 95% CI: 1.4 to 2.0) and PLWH (ratio: 2.3; 95% CI: 1.7 to 3.2) referred per index participant. Conclusions: Combining three distinct HIV testing and referral strategies increased the detection of previously undiagnosed HIV infections within the socio‐sexual networks of PLWH seeking STI care. Combination HIV detection strategies that leverage AHI screening and socio‐sexual contact networks offer a novel and efficacious approach to increasing HIV status awareness.